Food hygiene awareness among food handlers at night market / Puteri Anis Mazreen Zakaria dan Farah Nat Asya Ishak - Zakaria, Puteri Anis Mazreen; Ishak, Farah Nat Asya (Faculty of Hotel and Tourism, 2017)
The study is about Food Hygiene Awareness among Food Handlers at Night Market. The objectives are to identify the food hygiene knowledge of the food handlers at night market. Other than that it also to determine the practices of food handlers at night market towards food hygiene. Furthermore, this study is to know the factor that influences customer to visit night market. There are three research questions that contain in this research which are the knowledge level of the food handlers at night market about the food hygiene, the practices of food handlers at night market towards food hygiene and the factors that influence customer to visit night market. This research used secondary data in order to collect the data where the researcher needs to argue and criticize the information that had been collected from other sources. In addition, the data collection procedure has been derived from several sources like journal article, trusted blogs, website journal, organizational, books and others reliable sources. For this research, the researcher will find all the information from the reliable sources that had been stated above and argue the information. As conclusion, this study different than other study because this study discuss more depth about the factor that attract customer come to night market, knowledge level of food handlers about food hygiene at night market and their practices towards the food handler’s knowledge.